DESIGN OF PEOPLE PROFILING AND MODELING REPUTATION COMPUTATION BASED ON SENTIMENT ANALYSIS - Ahmad Mafazi Damanhuri; Zhang Huaping (Universitas Mercu Buana, 2019)
The number of popular people is still growing because of the easiness to access information technology. Every time people upload things and let people watch it and give it a like or comment. People who can impress other people will grow their popularity and fame. Some famous people make influences, help poor people with powers, and others are causing troubles. Community these days drives people perspective by share their thoughts on social media. They spread information and makes others want to see things they are talked about. Troublesome popular people defended by their fan base and attacked by other communities. By these cases, the research tried to gather information on social media and used it for calculation and profiling. The method that proposed to rely on this information is based on sentiment analysis to look up someone’s record and listing them into top 10 best got from DBpedia. This system shows the list of people and contains all important record about that person which can be used for decision support for a policy or rewarding people. The results have successfully visualized the output in the list of people with any further details following by clicking their names.